ISOLASI DAN IDENTIFIKASI STREPTOMYCETES DARI RIZOSFER JAGUNG (ZEA MAYS L.) YANG BERPOTENSI SEBAGAI PENGHASIL ANTIBIOTIKA - Ambarwati, Ambarwati; Soegihardjo, C. J.; Sembiring, Langkah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
In attempt to understand the diversity of Actinomycetes that is potential to be antibiotic producer, Streptomycetes were isolated and identified from soil sample taken from rhizosphere and non-rhizosphere of corn (Zea mays L.). The best antibiotic producers were identified by Scanning Electron Microscopy analysis and the identification of antibiotic produced conducted by using Thin Layer Chromatography analysis. The result of the study showed that 58 isolates were assigned to 17 colour groups. Ten isolates among the representatives of 17 colour groups were found potential to be antibiotic producer. Four isolates out of 10 isolates could inhibit both Staphylococcus aureus ATCC 25923 and Bacilus subtilis FNCC 0060, one isolate could inhibit only Staphylococcus aureus ATCC 25923 and five isolates could inhibit only Bacilus subtilis FNCC 0060. But no isolate could inhibit Escherichia coli ATCC 35218 and Salmonella typhimurium FNCC 0164. Among 10 isolates of antibiotic producer it was found that only one isolate (RNJ14) could strongly inhibit Staphylococcus aureus ATCC 25923 with inhibition zone diameter of 32.33 mm. On the bases of Thin Layer Chromatography analysis, the antibiotic produced by the isolate RNJ14 was identified to be lincomycin. Therefore it could be concluded that streptomycetes isolated from the rhizosphere and non-rhizosphere of corn (Zea mays L.) were potential to produce antibiotic.